The Leadership Role of Junior High School Principals in Maintaining Institutional Sustainability in the Covid-19 Era: Peran Kepemimpinan Kepala Sekolah Menengah Pertama dalam Mempertahankan Keberlanjutan Lembaga di Era Covid-19 - Ahmad, Ahmad; Haryanto, Budi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to identify how the role of the head of SMP Muhammadiyah 10 Sidoarjo in maintaining the sustainability of the institution in the covid-19 era. In maintaining the sustainability of the institution in the covid-19 era, the principal must also have a role as a manager, which is conceptual by planning, solving problems at school, organizing and collaborating with school internal parties and the wider community. leader, leader or leader must be able to show himself as a leader and be able to give confidence to teachers and employees in carrying out their duties properly in the era of the Covid-19 pandemic. Innovators, school principals must provide new ideas to school residents in order to maintain the sustainability of the institution. The motivator for the COVID-19 pandemic situation, the principal hopes to always provide encouragement to teachers and employees in order to foster enthusiasm in helping the principal. Types of field research with qualitative research methods. The main sources and types of data are data taken directly from school principals, vice principals (wakasek), public relations, treasurers, teachers, and administration (TU). The data collection methods are observation, interview, interview and documentation. Researchers conducted data analysis with the stages of data reduction, presentation, conclusion drawing and the validity of the data. So, the conclusion of this study shows that the role of the head of SMP Muhammadiyah 10 Sidoarjo in maintaining the sustainability of the institution in the Covid-19 era is quite good because nothing is sacrificed.